Students' Mathematical Problem-Solving Ability Based on Cognitive Style in Flipped Classroom Learning Model Assisted by Sevima Edlink - Mukarromah, Siti; Junaedi, Iwan (Unnes Journal of Mathematics Education, 2023)
This research aims were to (1) test the effectiveness of the Flipped Classroom learning model assisted by the Sevima Edlink on students' mathematical problem-solving abilities, and (2) describe students' mathematical problem-solving abilities based on cognitive style in the Flipped Classroom learning model assisted by the Sevima Edlink. This research was a mixed methods type of sequential explanatory design. Quantitative methods were used to test the effectiveness of using the Flipped Classroom learning model on students' mathematical problem-solving abilities while qualitative methods were used to describe students' mathematical problem-solving abilities based on cognitive style in the Flipped Classroom learning model assisted by the Sevima Edlink. Data collection was carried out using problem-solving ability tests, GEFT tests (cognitive style tests), and interviews. The population of this study were all class VIII students of SMP N 1 Pecangaan for the 2022/2023 school year. The samples used were students of class VIII E as the experimental group and class VIII G as the control group. The results of the research conducted showed that (1) the Flipped Classroom learning model was effective in increasing students' mathematical problem-solving abilities, (2) students' mathematical problem-solving abilities in terms of cognitive style were divided into two categories, namely FI (7) and FD (15). The FI category is divided into 3 patterns of problem-solving abilities while students with the FD category are divided into 5 patterns.